AceDRG: a stereochemical description generator for ligands. Issue 2 (1st February 2017) - Long, Fei; Nicholls, Robert A.; Emsley, Paul; Gražulis, Saulius; Merkys, Andrius; Vaitkus, Antanas; Murshudov, Garib N.
Abstract : The program AceDRG generates accurate stereochemical descriptions, and one or more conformations, of a given ligand. The program also analyses entries and extracts local environment‐dependent atom types, bonds and angles from the Crystallography Open Database. Abstract : The program AceDRG is designed for the derivation of stereochemical information about small molecules. It uses local chemical and topological environment‐based atom typing to derive and organize bond lengths and angles from a small‐molecule database: the Crystallography Open Database (COD). Information about the hybridization states of atoms, whether they belong to small rings (up to seven‐membered rings), ring aromaticity and nearest‐neighbour information is encoded in the atom types. All atoms from the COD have been classified according to the generated atom types. All bonds and angles have also been classified according to the atom types and, in a certain sense, bond types. Derived data are tabulated in a machine‐readable form that is freely available from CCP 4. AceDRG can also generate stereochemical information, provided that the basic bonding pattern of a ligand is known. The basic bonding pattern is perceived from one of the computational chemistry file formats, including SMILES, mmCIF, SDF MOL and SYBYL MOL2 files. Using the bonding chemistry, atom types, and bond and angle tables generated from the COD, AceDRG derives the `ideal' bond lengths, angles, plane groups, aromatic rings and chirality information, and writes them to an mmCIF file that can be used by the refinement program REFMAC 5 and the model‐building program Coot . Other refinement and model‐building programs such as PHENIX and BUSTER can also use these files. AceDRG also generates one or more coordinate sets corresponding to the most favourable conformation(s) of a given ligand. AceDRG employs RDKit for chemistry perception and for initial conformation generation, as well as for the interpretation of SMILES strings, SDF MOL and SYBYL MOL2 files.